USE OF RESOURCES AND ACTIVITIES FOR LANGUAGE LEARNING BEYOND THE CLASSROOM BY ENGLISH-MAJORED STUDENTS AT A UNIVERSITY IN VIETNAM - Khanh, Nguyen Vu; Le, Truong Bach; Chien, Duong Anh (VNU Journal of Foreign Studies; Vol 37 No 6DO - 10.25073/2525-2445/vnufs.4781, 2021)
This paper was part of a large-scale research into the use of resources and activities for English language learning after class time by English-majored students at a university in Vietnam. To explore the range of resources and activities frequently used by the researched students, a survey questionnaire was delivered online to 200 respondents via Google Form. The results revealed that online/computer-based/mobile-based and traditional broadcast materials were the most preferred resources for English language learning outside the classroom, whereas Watch YouTube , Listen to songs , Surf the Internet, and Use social media were the activities with the highest frequency of use. In addition, the self-directed naturalistic language learning activities were prevalent among the subjects, followed by self-instruction ones. By contrast, the studied participants tended to avoid taking part in activities that involved naturalistic language learning .